A revised checklist and key to the genus Podocinum Berlese (Acari: Podocinidae) with description of a new species from Tibet, Southwest China - Yan, Yi; Jin, Dao-Chao; Wu, Dian; Guo, Jian-Jun; Guo, Xian-Guo (Zootaxa, 2012)
The family Podocinidae Berlese is reported from the Qinghai-Tibet Plateau in Southwest China for the first time, on thebasis of a new species, Podocinum tibetensis sp. nov. A revised global checklist of the genus Podocinum is provided, in-cluding distribution information and bibliography for all species. A revised key for all known species of Podocinum isalso provided, based on the adult females. The new species increases the Chinese fauna of Podocinum to 12 species and the global fauna to 30 species.